Surface Electromyographic Responses During Rest on Mattresses with Different Firmness Levels in Adults with Normal BMI - Xiaohong Hu; Yuhong Gao; Keyang Liu; Luyao Xiang; Bin Luo; Li Li (Sensors)
Mattress firmness is a critical factor influencing sleep quality. This study investigates the effects of time, mattress firmness, and anthropometric parameters on surface electromyographic (sEMG) activity during supine rest. Eleven participants were analyzed, and the RMS values for lower back sEMG on three mattresses were measured as 8.37 ± 0.85 μV, 8.43 ± 1.06 μV, and 7.77 ± 1.15 μV during the final five minutes of testing, showing no statistical significance. Similarly, no significant differences in electromyographic activity were observed across different time periods. Anthropometric parameters such as BMI, waist circumference (WC), and waist-to-hip ratio (WHR) significantly influenced sEMG activity on firm mattresses. Higher BMI, waist circumference, and waist-to-hip ratio were negatively correlated with RMS and iEMG values on firm mattresses, suggesting that firmer mattresses are better suited for individuals with higher BMI, larger waist circumference, and a more balanced distribution of body weight between the upper and lower body. The medium-firm mattress had the lowest discomfort scores, indicating its broader adaptability. These findings provide a foundation for designing ergonomically optimized, personalized mattresses to improve sleep quality across diverse populations.